School Environment and Dentoalveolar Trauma in Public Schools of Xaxim, Brazil - Monica Zeni Refosco; Marcos Britto Corrêa; Lucimare Ferraz; Sinval Adalberto Rodrigues Junior (Association of Support to Oral Health Research (APESB), 2016)
Objective:To assess the environment of elementary public schools of Xaxim, SC, Brazil, targeting the prevention of dental trauma.Material and Methods:All thirteen public schools in the city of Xaxim had their physical structure assessed concerning the conditions of floors, windows, stairs, capacity, type of surface of the schoolyard, number of supervisors during recess, and social inclusion. The social environment was assessed through the application of the Brazilian National School-Based Health Survey (PeNSE) to either school principals or educational coordinators. Regarding the social environment, areas for student physical activities, episodes of violence (swearing, physical and verbal aggression), and cases of robbery and theft in the school environment were assessed. Data were analyzed by descriptive statistics.Results:Situations considered of risk for the occurrence of accidents and dental trauma were identified. Most schools presented episodes of swearing and fights among students, as well as inadequate physical environment.Conclusion:Both social and physical environments were favorable to the occurrence of dental trauma; however, studies that establish this relationship in a deeper fashion are still necessary.